Trauma, memory, and cultural healing: ecofeminist parallels in Toni Morrison’s Beloved and Saratchandra Chattopadhya’s Srikanta - Nehal, Sarder Ragib (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.